The investigation of the calcium antagonist nifedipine on fetal umbilical artery Doppler waveforms - Puzey, Martin Stanley (Department of Obstetrics and Gynaecology, 2018)
The following thesis will describe the investigation of the effect of nifedipine (a calcium antagonist) on the Doppler flow velocity waveform of the umbilical artery. The thesis is divided into two parts. The first section is a literature review of the three main aspects of the thesis namely: 1. The uteroplacental circulation in humans and the pathophysiology related to this circulation in hypertension and intrauterine growth retardation (IUGR). 2. The biokinetics of nifedipine and a review of the experiments that have been performed using the drug in human and animal models. 3. The principles of Doppler ultrasound and the literature pertaining to its use in the study of the uteroplacental circulation. The second part of the thesis is devoted to the effect of nifedipine on fetal umbilical artery Doppler waveform analysis. In the first ·stage of the investigation the effect of the drug on hypertensive mothers has been examined, and in the second stage the effect on fetuses that have an increased resistance index of the umbilical artery Doppler waveform.